Infection Control Measures In Response To Epidemics And Pandemics: Lessons Learned And Best Practices (Journal of Namibian Studies : History Politics Culture, 2023)
Epidemics and pandemics pose significant challenges to public health systems worldwide, necessitating swift and effective infection control measures to mitigate their impact. This article examines the key infection control measures deployed during recent epidemics and pandemics, drawing on lessons learned and identifying best practices for future outbreaks. From the Ebola outbreak in West Africa to the ongoing COVID-19 pandemic, various strategies have been employed to contain the spread of infectious diseases and protect public health. This article explores the roles of surveillance, quarantine, social distancing, personal protective equipment (PPE), vaccination campaigns, and public health communication in epidemic and pandemic response. Additionally, it highlights the importance of international cooperation and coordination in combating global health threats. By synthesizing experiences from past outbreaks, this article aims to inform policymakers, healthcare professionals, and the general public about effective infection control measures to safeguard communities during epidemics and pandemics.